IN VITRO SUSCEPTIBILITY TO 11 ANTIMICROBIAL AGENTS OF Escherichia coli ISOLATED FROM DIARRHEIC AND MASTITIC CATTLE IN SÃO PAULO STATE, BRAZIL. - BAPTISTA, A.; MARIN, J. M. (Ars Veterinaria, 2008)
Emergence of bacterial antimicrobial resistance has become a serious worldwide problem. Antimicrobial susceptibility testing was performed on a total of 150 Escherichia coli isolates from diarrheic, mastitic and control cattle. Among the 11 antimicrobial agents tested, resistance was most frequently found for ampicillin, streptomycin and tetracycline in isolates from the diarrheic and mastitic groups. The isolates from the control group were susceptible to all agents tested. Multidrug resistance was found among 30.0% of the isolates from the diarrheic group and among 14.0% from the mastitic group. The potential of the transfer of antimicrobial resistance by enteric bacteria from animals used as food source to human populations is a cause of concern. Surveillance is an essential part of a policy of rational use of antimicrobial agents and should lead to regular and continuous monitoring of the antimicrobial bacterial resistance to avoid its increase among animal faecal flora. KEY-WORDS: Escherichia coli. Antimicrobial resistance. Bovines. Surveillance.